2021
DOI: 10.46827/ejes.v8i3.3660
|View full text |Cite
|
Sign up to set email alerts
|

Science Performance and Scholastic Aptitude of Grade 9 Learners

Abstract: This study determined the relationship between scholastic aptitude comprised of reading comprehension, verbal ability, mathematical ability, logical reasoning ability, and visual manipulative skills and Science performance of Grade 9 learners in a privately run basic education institution in Lapu-lapu, Cebu, Philippines during the school year 2015-2016. Descriptive and correlational research designs were carried out to assess the relationship among the identified variables. The study anchored its framework on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
3
6
0
Order By: Relevance
“…Thai et al (2017) pointed out that learning environments wherein feedback is delivered promptly would lead to higher learning performance. This supports the findings of Nadolski and Hummel's (2017) study, which stated that feedback should be given regularly and in a reasonable timeframe since the more closely the feedback relates to actual performance, the more strongly it will affect future performance, aptitude (Mingoa & Abocejo, 2021), and student motivation. However, Cheng (2017) asserted that providing written feedback is a time-consuming task and that it can be challenging for teachers to do so on a regular basis.…”
Section: Resultssupporting
confidence: 84%
“…Thai et al (2017) pointed out that learning environments wherein feedback is delivered promptly would lead to higher learning performance. This supports the findings of Nadolski and Hummel's (2017) study, which stated that feedback should be given regularly and in a reasonable timeframe since the more closely the feedback relates to actual performance, the more strongly it will affect future performance, aptitude (Mingoa & Abocejo, 2021), and student motivation. However, Cheng (2017) asserted that providing written feedback is a time-consuming task and that it can be challenging for teachers to do so on a regular basis.…”
Section: Resultssupporting
confidence: 84%
“…As likewise indicated by the grand mean of 91, the result shows that, while aptitude in mathematics and science subjects may help determine scholastic performance (Mingoa & Abocejo, 2021), particularly in specialized subjects, the STEM students who are not inclined in those disciplines may still excel, and that logical or visual intelligence types may not be the only measure (Mimid et al, 2020) of students' success in STEM.…”
Section: Resultsmentioning
confidence: 83%
“…This is in accordance with the research of Tek et al (2012) which shows that in general, senior high school students in Malaysia have not acquired science process skills as expected by the Malaysian Ministry of Education. In addition, the findings of Derilo (2019) also found that most students in the Philippines had low and insufficient levels of science process skills. In addition, in the South Asian continent such as Sri Lanka and Bangladesh also found the same thing, namely the low science process skills of students.…”
Section: Introductionmentioning
confidence: 91%